Pengetahuan Ibu dan Pengelolaan Demam Anak di Satu Rumah Sakit Swasta di Indonesia Barat - Adiyat Rachmawati; Lia Kartika (JURNAL KEPERAWATAN RAFLESIA, 2020)
Child's fever become a special consideration for mothers because of the adverse effects that arise if the fever is not treated. Mothers can experience anxiety so that independent treatment is the most effort made. Unaccountable information can lead mothers to inappropriate fever management. Preliminary data taken randomly in the outpatient unit showed that 9 out of 15 mothers did not understand the understanding and management of children's fever. The purpose of the study was to determine the relationship of maternal knowledge about child fever with the management of child fever in a private hospital in Western Indonesia. This descriptive correlational quantitative study using a cross-sectional approach was conducted in February - March 2020. The incidental sampling technique obtained 191 respondents from the initial population ie all child clients in the outpatient unit. Data collection using a questionnaire about maternal knowledge and management of children's fever owned by Widyastuti, 2016 with a content validity index of 0.88. The reliability of the mother's knowledge questionnaire reached Cronbach Alpha 0.527 and the children's fever management questionnaire reached 0.724 with the KR-20 technique. Chi Square analysis showed a significant relationship between mother's knowledge and management of children's fever (p = 0.001). Providing education about comprehensive fever management is very much needed in the outpatient unit setting. The next recommendation is to conduct research to determine the perceptions and attitudes of mothers about child fever and its management.